Global Activity in the field of Safeguard Measures in 2022. Stocktaking in the light of notifications made to the WTO Committee on Safeguard - Piérola-Castro, Fernando (Latin American Journal of Trade Policy, 2023)
Overview of global activity regarding the conduct of safeguard investigations and the imposition or extension of safeguard measures during the year 2022, in light of notifications made by WTO members in that year.